Population Assessment and Appropriate Spraying Technique to Control The Bagworm (Metisa plana Walker) in North Sumatra And Lampung - Sudarsono, Hamim; Purnomo, Purnomo; Hariri, Agus M. (AGRIVITA, Journal of Agricultural Science, 2011)
Over the last few years, the bagworm Metisa plana Walker (Lepidoptera: Psychidae) has become an important pest of oil palm, especially in North Sumatra. Recent report suggested that the bagworm has also been found in Lampung. The report requires preliminary survey to assess M. plana status and to prepare an effective control measure for the pest. This study was conducted to determine the relative density of M. plana in North Sumatra and Lampung and to compare the effectiveness of the spraying versus fogging application to control M. plana in oil palm fields. The observation confirmed that in 2010 M. plana colonies have developed in Lampung with an average relatively similar to that in North Sumatra during 2005. The finding implies that monitoring should be taken routinely to anticipate further development of the bagworm population in Lampung. Overall results of carbosulfan treatments suggested that the fogging insecticide technique was potentially as effective as spraying technique. This finding could be beneficial for bagworm control program due to the extensive areas of oil palm and the large size of canopy. A more thorough experiment is required to explore the most economical doses and to select effective insecticides to control M. plana. Keywords : Metisa plana Walker (Lepidoptera: Psychidae), bagworm, oil palm, spraying vs. fogging application